2021
DOI: 10.1007/s11562-020-00458-8
|View full text |Cite
|
Sign up to set email alerts
|

Care in practice: negotiations regarding care for the elderly in multigenerational Arab Muslim families in Denmark

Abstract: Recent studies conclude that ethnic minority families in Denmark tend to be dismissive of senior housing and municipal homecare services for elderly family members. A large proportion of Muslim minority families in Denmark attach great importance to caring for the elderly as a tradition and prefer to take care of their own elderly family members at home. Nevertheless, the fact that morality, incentives, and obligations in relation to care for the elderly may be legitimized and/or contested with reference to cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…A few caregiver participants, who migrated to Europe with their parents in early childhood, asserted that they will be less dependent on their children in their old age [ 45 , 47 ], and said the younger generation (who were born and raised in Europe) may not be so dedicated to the caring norms espoused by older family members [ 47 ]. The younger generations’ perceptions of caregiving were found to be less influenced by the older adults’ definition of ideal caregiving, and they described it as a sense of duty [ 41 , 44 , 49 ]. One participant aged 23 with Palestinian background and living in Denmark who contributes (along with her father and other siblings) to the care of her grandmother said, “ She (grandmother) says: are you here to take care of me or to do your own stuff?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few caregiver participants, who migrated to Europe with their parents in early childhood, asserted that they will be less dependent on their children in their old age [ 45 , 47 ], and said the younger generation (who were born and raised in Europe) may not be so dedicated to the caring norms espoused by older family members [ 47 ]. The younger generations’ perceptions of caregiving were found to be less influenced by the older adults’ definition of ideal caregiving, and they described it as a sense of duty [ 41 , 44 , 49 ]. One participant aged 23 with Palestinian background and living in Denmark who contributes (along with her father and other siblings) to the care of her grandmother said, “ She (grandmother) says: are you here to take care of me or to do your own stuff?…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, my cousins have accustomed her to ask them to do whatever she wants them to do. To be honest, I do not enjoy her company, but I feel like it is my duty” [ 44 ]. As such, younger generations were found to have more leeway from the home country’s caregiving perspective and therefore had more flexibility in choosing alternatives to providing informal care [ 41 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the Environmental domain, we found that aging (increase in age) is positively correlated with the domain. This could be attributed to the spiritual practices and religious beliefs of Arab Muslim families which encourage them to provide support to elderly and make them perceive caring for elderly family members as filial piety and a Family obligation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The condition of Islamic boarding schools allows for an academic atmosphere because Kiai (teachers) and students (santri) are part of a parenting pattern capable of developing broad-minded and skilled individuals [66]. Pesantren also plays a role in helping people from the lower classes enjoy education and can learn to become successful people in their lives [67].…”
Section: Islamic Boarding School (Pesantren)mentioning
confidence: 99%